In vitro evaluation of novel reverse transcriptase inhibitors TAF (tenofovir alafenamide) and OBP-601 (2,3-didehydro-3-deoxy-4-ethynylthymidine) against multi-drug resistant primary isolates of HIV-2 - Bártolo, Inês (2019)
New antiretroviral drugs are needed to treat HIV-2 infected patients failing therapy. Herein, we evaluate the activity of novel reverse transcriptase inhibitors tenofovir alafenamide (TAF) and OBP-601(2,3-didehydro-3-deoxy-4-ethynylthymidine) against primary isolates from HIV-2 infected patients experiencing virologic failure. TAF and OBP-601 were tested against twelve primary isolates obtained from nine drug-experienced patients failing therapy and three drug naïve patients using a single-round infectivity assay in TZM-bl cells. The RT-coding region of pol was sequenced and the GRADE algorithm was used to identify resistance profiles and mutations. TAF and OBP-601 inhibited the replication of almost all isolates at a median EC50 of 0.27 nM and 6.83 nM, respectively. Two isolates showed moderate-level resistance to OBP-601 or TAF and two other isolates showed high-level resistance to OBP-601 or to both drugs. With one exception, all resistant viruses had canonical nucleoside reverse transcriptase inhibitors (NRTIs)-associated resistance mutations (K65R, N69S, V111I, Y115F, Q151M and M184V). Our results show that TAF has potent activity against most multi-drug resistant HIV-2 isolates and should be considered for the treatment of HIV-2 infected patients failing therapy.